PENINGKATAN PERILAKU CARING PERAWAT MELALUI CHARACTER BUILDING TRAINING - Firmansyah Firman Firman (Stikes Graha Edukasi Makassar, 2018)
Objective: To Know caring behavior of nurse and lack of motivation and commitment of nurse executing in serving patient. Methods: Data collection using interview, questionnaire, FGD, documentation study and observation on head of nursing, development section, monitoring and evaluation section, 12 headroom, 26 nurses, and 40 patients Output: After character building training workshop at nurse there was an increase in caring behavior of nurses including communication, commitment, and motivation from 44.7% to 96.3%. Discussion: The management of nursing services is a fundamental and important part of the overall management of nursing services in the hospital which is a barometer of health service performance improvement. Nursing which is the main gateway of nursing service providers in hospitals must provide excellent service, efficient, and professional to the community. Conclusion: To maintain caring behavior of nurses, it is required a joint commitment from the executing nurse, the team leader, the head of the room, the nursing committee, the nursing field and all those involved in the health service in order to be able to present the optimal quality of nursing service